2016
DOI: 10.1111/mec.13414
|View full text |Cite
|
Sign up to set email alerts
|

Germline DNA methylation in reef corals: patterns and potential roles in response to environmental change

Abstract: DNA methylation is an epigenetic mark that plays an inadequately understood role in gene regulation, particularly in non-model species. Because it can be influenced by the environment, DNA methylation may contribute to the ability of organisms to acclimatize and adapt to environmental change. We evaluated the distribution of gene body methylation in reef-building corals, a group of organisms facing significant environmental threats. Gene body methylation in six species of corals was inferred from in silico tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
91
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 45 publications
17
91
1
Order By: Relevance
“…However, studies in turtles and alligators have also found different methylation patterns in other sex determination genes. For example, promoter methylation at SOX9 showed a converse methylation pattern Dimond & Roberts (2016) compared to cyp19a1 in alligator gonads (Parrott et al, 2014). These results suggest that DNA methylation could act as a key mediator integrating temperature into molecular mechanisms that determine sex in some animal species.…”
Section: Within-generational Epigenetic Effectsmentioning
confidence: 84%
See 1 more Smart Citation
“…However, studies in turtles and alligators have also found different methylation patterns in other sex determination genes. For example, promoter methylation at SOX9 showed a converse methylation pattern Dimond & Roberts (2016) compared to cyp19a1 in alligator gonads (Parrott et al, 2014). These results suggest that DNA methylation could act as a key mediator integrating temperature into molecular mechanisms that determine sex in some animal species.…”
Section: Within-generational Epigenetic Effectsmentioning
confidence: 84%
“…To study the epigenetic basic of phenotypic variation, it is useful for a system to exhibit a significant degree of phenotypic plasticity when responding to environmental changes (Dimond & Roberts, 2016). Good long-term data sets connecting environmental parameters with changes in phenotype and gene expression can also help to place functional work within a broader environmental context.…”
Section: Box 4 Outstanding Questions About Epigenetically Encoded Thementioning
confidence: 99%
“…Furthermore, the low levels of correlation found between the transcriptome and the methylome of several multicellular organisms 32,33 , combined with the lack of a CpG methylation system in some of the most widely studied model animals, including the fruit fly Drosophila and the roundworm Caenorhabditis 34,35 , weakens the case for its significance as a universal regulator of gene expression 15,36 , and hence a universal mediator of TGP. In corals, DNA methylation levels correlate strongly with gene function; broadly and uniformly expressed 'housekeeping' genes are strongly methylated, whereas genes responsible for inducible or cell-specific functions are weakly methylated 37,38 (Fig. 2).…”
Section: Box 1 | the Pace Of Genetic Adaptationmentioning
confidence: 99%
“…Studies on plants have dominated the literature on ecological epigenetics (Schrey et al, 2013;Baulcombe and Dean, 2014;Verhoeven et al, 2016), especially in response to stress (Wang et al, 2011;Grativol et al, 2012;Al-Lawati et al, 2016). On the marine side, epigenetic and epigenomic approaches are being used to explore areas such as (1) sources of phenotypic plasticity, as created by differential gene expression (Dixon et al, 2014;Dimond and Roberts, 2016;Marsh et al, 2016), (2) mechanisms involved in development (Riviere et al, 2013), and (3) a possible rapid response to anthropogenic environmental change (Putnam et al, 2016). These studies are mechanistic, but importantly also bridge to understanding adaptive capacity of marine organisms in response to environmental change (Calosi et al, 2016).…”
Section: Epigenetics-a Brief Overviewmentioning
confidence: 99%